2017
DOI: 10.1177/1744629516686571
|View full text |Cite
|
Sign up to set email alerts
|

Dietary practices of children and adolescents with Down syndrome

Abstract: The aim of this study was to assess dietary intake, breastfeeding history, weight at birth and current weight in children and adolescents with Down syndrome (DS). Therefore, a cross-sectional, controlled study with 19 DS participants and 19 controls without DS matched by gender and age was performed. Except for vitamin D, a lower or the same frequency of insufficient intake in other micronutrients was noted in participants compared with controls. The DS group had a reduced exclusive breastfeeding duration and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
56
2
8

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(66 citation statements)
references
References 17 publications
0
56
2
8
Order By: Relevance
“…Such an attitude and unwarranted use of the elimination diet may be associated with the improper content of nutrients in the diets of the subjects. In the study by Magnesis et al, regarding diets of children with DS, numerous nutritional errors were observed, such as an increased intake of carbohydrates and calories as well as sodium, accompanied by insufficient intake of calcium, certain B vitamins, and water [27]. In other studies, a high-carbohydrate diet rich in simple carbohydrates and with a deficiency of vitamins and minerals was also observed [7,28].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Such an attitude and unwarranted use of the elimination diet may be associated with the improper content of nutrients in the diets of the subjects. In the study by Magnesis et al, regarding diets of children with DS, numerous nutritional errors were observed, such as an increased intake of carbohydrates and calories as well as sodium, accompanied by insufficient intake of calcium, certain B vitamins, and water [27]. In other studies, a high-carbohydrate diet rich in simple carbohydrates and with a deficiency of vitamins and minerals was also observed [7,28].…”
Section: Discussionmentioning
confidence: 99%
“…Children ate sweets several times a week, every day, or even several times a day [29,30,32,34]. Magenis et al, however, showed high carbohydrate intake among children with DS [27].…”
Section: Discussionmentioning
confidence: 99%
“…Al evaluar la necesidad de estudios de función renal en este grupo, una buena propuesta sería agregarlo a los exámenes de rutina que ellos requieren anualmente, aprovechando el mismo momento de toma de muestra, sin embargo, pareciera relevante considerar algunos puntos a la hora de interpretar los resultados: 1) Sería importante conocer la función renal en aquellos con mayor riesgo, tales como pacientes con cardiopatías congénitas hemodinámicamente significativas y que requerirán de cardiocirugía; antecedentes de malformaciones nefrourológicas; usuarios de medicamentos nefrotóxicos o de uso de medios de contraste endovenoso; antecedentes familiares de riesgo para desarrollar nefropatías, entre otras; 2) Conocer las diferencias en el metabolismo de uratos descritas en este grupo, considerando que frente a niveles de urea elevada no se ha descrito asociación con gota más que en reportes de casos aislados [4][5][6] , incluso en uno de esos reportes refieren que la condición de sín-drome de Down suprimiría la aparición de artritis por esta causa, ya que los niveles de uricemia necesarias para desarrollar artritis son mayores que las persodOI: 10.4067/S0370-41062017000300020 nas con gota sin síndrome de Down 6 ; 3) Considerar la alta frecuencia de la dificultad para tomar agua, lo que hemos observado en el gran grupo en seguimiento y descrito en literatura reciente 7 , por lo que es muy frecuente encontrar con nitrógeno ureico plasmático sutilmente elevado frente a situaciones de poca hidratación o por las horas de ayuno necesario para la toma de exámenes. En la experiencia de nuestro Centro nos hemos encontrado con un grupo importante de niños estudiados en forma exhaustiva por nitrógeno ureico levemente elevado, que simplemente estaban en un contexto de deshidratación.…”
Section: Respuesta Carta Al Editorunclassified
“…Mothers of babies with DS have difficulty breastfeeding (6) . Studies on the prevalence of breastfeeding in babies with DS have identified lower rates than in the general population (12) and a reduction in breastfeeding duration in these babies with DS (13) .…”
Section: Introductionmentioning
confidence: 99%